A differential game analysis of multi-regional coalition for transboundary pollution problems - Zuliang Lu; Fei Cai; Ruixiang Xu; Xiankui Wu; Chunjuan Hou; Yin Yang (Ecological Indicators, 2022)
Basin water pollution control problem has become a real and serious challenge to build an environment-friendly and resource-conserving society. Since the water environment is quasi-public property, regional cooperation across upstream and downstream regions is critical for pollution control. Employing the differential game theory, we establish four differential game models of transboundary pollution with multi-regional coalitions. Optimal control theory was used to explore the optimal feedback Nash equilibriums solutions of the four models. Our analysis suggests that cooperation among the three regions is more effective in pollution control. The upstream and midstream cooperation can help the upstream region to increase the pollution abatement level, decrease the pollution emission level and pollution stock. The cooperation between the midstream region and both the upstream and downstream regions can help the midstream region to increase the pollution abatement level and decrease the pollution emission level.